(untitled) (Eurasian Journal of Learning and Academic Teaching, 2024)
An English for Specific Purposes (ESP) course designed specifically for Uzbek medical professionals is examined in this study. Through the use of problem-based learning (PBL), the course meets the demands of the learners in terms of professional contacts, patient communication, and medical terminology. Through the use of formative evaluation techniques and a thorough requirements analysis, the course guarantees relevance and real-world application. There is discussion of obstacles to overcome, such as juggling medical and language skills. The results provide useful information for ESP course designers worldwide, indicating that the incorporation of interactive techniques and medical scenarios greatly improves language learning and professional competency